THE MAIN CLASSES OF YOUTH SOCIOLECTISMS IN THE RUSSIAN LANGUAGE - Akramova Nozima Muzaffarovna (Western European Studies, 2024)
The article under discussion depicts the main types of youth socilectisms. The conducted research allows to assert that socilectisms function in the modern discourse of youth – word-forming derivatives of different parts of speech, built in accordance with the most different ways of word-formation in the Russian language.
Keywords: sociolect; sociolectism; phraseological; young people